If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3c + -17 = 5c + -11 Reorder the terms: -17 + 3c = 5c + -11 Reorder the terms: -17 + 3c = -11 + 5c Solving -17 + 3c = -11 + 5c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-5c' to each side of the equation. -17 + 3c + -5c = -11 + 5c + -5c Combine like terms: 3c + -5c = -2c -17 + -2c = -11 + 5c + -5c Combine like terms: 5c + -5c = 0 -17 + -2c = -11 + 0 -17 + -2c = -11 Add '17' to each side of the equation. -17 + 17 + -2c = -11 + 17 Combine like terms: -17 + 17 = 0 0 + -2c = -11 + 17 -2c = -11 + 17 Combine like terms: -11 + 17 = 6 -2c = 6 Divide each side by '-2'. c = -3 Simplifying c = -3
| -x+8y=21 | | 10=w-19 | | 7a^2-a^2+16= | | 4(3-3x)-8x=8-2(5x+8) | | 10=w-9 | | 6-5(3x-5)=16 | | 3(2k+3)-11k=14 | | 3v-7-5=21 | | 0.6(n-6)=5n-43 | | 12v=14v-12 | | m+2n=9 | | 2a+3=-5 | | 5x+16=4x-2 | | 2a+9y-6e+1u-5k+4= | | (d+280)+d=2676 | | 11a=a+20 | | 8z^2+10z+3= | | d+16=8 | | 5x^2-55x-300=0 | | -18-6k=6(1+9k) | | 3x+9-6x=-35 | | 3m-2n=11 | | 6x+13-9x=15-19x+16x-2 | | t-17=6 | | 12-4x+8y=6y+3x+10 | | -8+x-6x=-8x+2x | | (-2x+3.5)-(x-1.2)= | | t+20=2t | | 5(2x-4+3x)=5(2x+-4+3x) | | 4(-4)-2h=-6 | | 23x-11-17x=3(2x-5)+4 | | 9(3+h)+2h=9.5 |